A simple traffic light approach to backtesting expected shortfall - Nick Costanzino; Michael Curran (Risks, 2018)
We propose a Traffic Light approach to backtesting Expected Shortfall which is completely consistent with, and analogous to, the Traffic Light approach to backtesting VaR (Value at Risk) initially proposed by the Basel Committee on Banking Supervision in their 1996 consultative document Basle Committee on Banking Supervision (1996). The approach relies on the generalized coverage test for Expected Shortfall developed in Costanzino and Curran (2015).
Keywords: 330; Expected Shortfall; backtesting; Fundamental Review of the Trading Book